1970
DOI: 10.1099/00221287-61-1-121
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Multiple Forms of Esterases in Rhizobium by Paper Electrophoresis

Abstract: SUMMARYFifty-two strains, comprising six Rhizobium species, were examined for their esterase patterns using electrophoresis on cellulose acetate. Esterase activity was detected in five Rhizobium species. The sixth species, R. japonicum, was characterized by the absence of esterase activity in all but one of the strains examined. Rhizobium trifolii and R. leguminosarum strains showed similarities in their esterase profiles. Rhizobium meliloti strains formed a group distinct from these on the basis of their este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Furthermore, with the exceptions of the studies of Pinero et al (31) and Eardly et al (11), the reported electrophoretic studies on Rhizobium species have been based on only a few enzyme loci. However, these studies have shown that numerous allelic variants exist for those loci examined (13,14,18,27,28,45,46). In this study, we examined 44 different enzyme loci, of which 28 loci provided staining of sufficient intensity and resolution for reliable genetic interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the exceptions of the studies of Pinero et al (31) and Eardly et al (11), the reported electrophoretic studies on Rhizobium species have been based on only a few enzyme loci. However, these studies have shown that numerous allelic variants exist for those loci examined (13,14,18,27,28,45,46). In this study, we examined 44 different enzyme loci, of which 28 loci provided staining of sufficient intensity and resolution for reliable genetic interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, allozyme data have proven valuable for characterizing strains in epidemiological studies (12), ecological studies (6), population structure (39), and systematics (37). With the exceptions of the recent studies of Pinero et al (31) and Eardly et al (11), most studies on Rhizobium strains (13, 14,18,27,28,45,46) have been based on the examination of a limited number of loci, which has precluded a reliable estimate of genetic relationships among the strains examined.…”
mentioning
confidence: 99%
“…At that time R. loti was distinguished from other fast-growing rhizobia on the basis of flagellation (l), esterase patterns (14), response to isoflavonoids (18), plant nodulation (11,12), internal antigens (23), electrophoresis of soluble cellular proteins (19,20), and DNA relatedness (4,8). More recently, cellular fatty acid analysis was used to reveal differences, useful for identification purposes, between strains of R. loti and strains of the genus Agrobacterium and other Rhizobium or Sinorhizobium species (10).…”
mentioning
confidence: 99%
“…(16), and Rhizobium spp. (19,20,34,35,50,51). Isozyme studies of Frankia strains have already presented evidence for diversity in some enzymes (40,45).…”
mentioning
confidence: 99%